A Modelling framework for assessing the economic impact of climate change in the Caribbean - Roson, Roberto (2013)
Provides a general description of the model and an illustrative simulation exercise. Highlights the fact that the Caribbean is a highly vulnerable region where climate change is expected to generate sizeable and negative economic consequences.